Neoadjuvant systemic therapy in melanoma: recommendations of the International Neoadjuvant Melanoma Consortium. Issue 7 (July 2019) - ,; Andrews, Miles C; Berry, Donald A; Block, Matthew S; Boland, Genevieve M; Bollin, Kathryn B; Carlino, Matteo S; Carvajal, Richard D; Cohen, Jonathan; Davar, Diwakar; Delman, Keith A; Dummer, Reinhard; et al.
Summary: Advances in the treatment of metastatic melanoma have improved responses and survival. However, many patients continue to experience resistance or toxicity to treatment, highlighting a crucial need to identify biomarkers and understand mechanisms of response and toxicity. Neoadjuvant therapy for regional metastases might improve operability and clinical outcomes over upfront surgery and adjuvant therapy, and has become an established role for drug development and biomarker discovery in other cancers (including locally advanced breast cancer, head and neck squamous cell carcinomas, gastroesophageal cancer, and anal cancer). Patients with clinically detectable stage III melanoma are ideal candidates for neoadjuvant therapy, because they represent a high-risk patient population with poor outcomes when treated with upfront surgery alone. Neoadjuvant therapy is now an active area of research for melanoma with numerous completed and ongoing trials (since 2014) with disparate designs, endpoints, and analyses under investigation. We have, therefore, established the International Neoadjuvant Melanoma Consortium with experts in medical oncology, surgical oncology, pathology, radiation oncology, radiology, and translational research to develop recommendations for investigating neoadjuvant therapy in melanoma to align future trial designs and correlative analyses. Alignment and consistency of neoadjuvant trials will facilitate optimal data organisation for future regulatory review and strengthen translational research across the melanoma disease continuum.